Towards an automated robotic arc-welding-based additive manufacturing system from CAD to finished part. (April 2016) - Ding, Donghong; Shen, Chen; Pan, Zengxi; Cuiuri, Dominic; Li, Huijun; Larkin, Nathan; van Duin, Stephen
Abstract: Arc welding has been widely explored for additive manufacturing of large metal components over the last three decades due to its lower capital cost, an unlimited build envelope, and higher deposition rates. Although significant improvements have been made, an arc welding process has yet to be incorporated in a commercially available additive manufacturing system. The next step in exploiting "true" arc-welding-based additive manufacturing is to develop the automation software required to produce CAD-to-part capability. This study focuses on developing a fully automated system using robotic gas metal arc welding to additively manufacture metal components. The system contains several modules, including bead modelling, slicing, deposition path planning, weld setting, and post-process machining. Among these modules, bead modelling provides the essential database for process control, and an innovative path planning strategy fulfils the requirements of the automated system. A user friendly interface has been developed for non-experts to operate the developed system. Finally, a thin-walled aluminium structure has been fabricated automatically using only a CAD model as the informational input to the system. This exercise demonstrates that the developed system is a significant contribution towards the ultimate goal of producing a practical and highly automated arc-welding-based additive manufacturing system for industrial application. Highlights: An automated arc-welding-based additive manufacturing system was reported. Integrated additive and subtractive manufacturing methodology was developed. Deposition paths and welding parameters were automatically generated. User interface using only CAD models as inputs was developed. The proposed automated system was verified experimentally.